Mining Investment Legal Certainty Under The Terms of Act No. 4 Of 2009 Concerning Mineral and Coal Mining and Act No. 25 of 2007 on Investment - Suroto Suroto; Gunarto Gunarto (Jurnal Daulat Hukum, 2018)
In this study the issues to be discussed in are: Mining Investment Legal Certainty According to provisions of Act No. 4 of 2009 on Mineral and Coal and Act No. 25 of 2007 on Investment. Based on the results of this study are Legality exploitation of minerals statutory number number 4 Legality exploitation of minerals statutory number number 4 of 2009 substantially only in a form that permit, in contrast to the legality of the concession at the time of the enactment of Act No. 1, 1967, consists of a wide variety of forms namely mining Authority (KP) contract of work (COW), mineral and agreements coal mining works (PKP2B) and SIPDs for extractive industry and artisanal mining licenses for artisanal mining. Various legality at the time of the enactment of Act No. 11 of 1967, led to the coordination, supervision and control of less than the maximum, because every legality issued to a mining business activity carried out not in a good coordination. Prior to the issuance of Act No. 25 of 2007 is still a very significant difference between foreign investors and domestic investors. This is evident from the provisions of legislation. Foreign investment is regulated in Act No. 1 of 1967 concerning Foreign Investment whereas domestic investment stipulated in Act No. 6 of 1968 on Domestic Investment.Keywords: Rule of Law; Mining; Investment.